Theory Extended_Nat

theory Extended_Nat
imports Countable Order_Continuity
(*  Title:      HOL/Library/Extended_Nat.thy
    Author:     David von Oheimb, TU Muenchen;  Florian Haftmann, TU Muenchen
    Contributions: David Trachtenherz, TU Muenchen
*)

section ‹Extended natural numbers (i.e. with infinity)›

theory Extended_Nat
imports Main Countable Order_Continuity
begin

class infinity =
  fixes infinity :: "'a"  ("∞")


subsection ‹Type definition›

text ‹
  We extend the standard natural numbers by a special value indicating
  infinity.
›

typedef enat = "UNIV :: nat option set" ..

text ‹TODO: introduce enat as coinductive datatype, enat is just @{const of_nat}›

definition enat :: "nat ⇒ enat" where
  "enat n = Abs_enat (Some n)"
 
instantiation enat :: infinity
begin

definition "∞ = Abs_enat None"
instance ..

end

instance enat :: countable
proof
  show "∃to_nat::enat ⇒ nat. inj to_nat"
    by (rule exI[of _ "to_nat ∘ Rep_enat"]) (simp add: inj_on_def Rep_enat_inject)
qed
 
old_rep_datatype enat "∞ :: enat"
proof -
  fix P i assume "⋀j. P (enat j)" "P ∞"
  then show "P i"
  proof induct
    case (Abs_enat y) then show ?case
      by (cases y rule: option.exhaust)
         (auto simp: enat_def infinity_enat_def)
  qed
qed (auto simp add: enat_def infinity_enat_def Abs_enat_inject)

declare [[coercion "enat::nat⇒enat"]]

lemmas enat2_cases = enat.exhaust[case_product enat.exhaust]
lemmas enat3_cases = enat.exhaust[case_product enat.exhaust enat.exhaust]

lemma not_infinity_eq [iff]: "(x ≠ ∞) = (∃i. x = enat i)"
  by (cases x) auto

lemma not_enat_eq [iff]: "(∀y. x ≠ enat y) = (x = ∞)"
  by (cases x) auto

primrec the_enat :: "enat ⇒ nat"
  where "the_enat (enat n) = n"


subsection ‹Constructors and numbers›

instantiation enat :: "{zero, one}"
begin

definition
  "0 = enat 0"

definition
  "1 = enat 1"

instance ..

end

definition eSuc :: "enat ⇒ enat" where
  "eSuc i = (case i of enat n ⇒ enat (Suc n) | ∞ ⇒ ∞)"

lemma enat_0 [code_post]: "enat 0 = 0"
  by (simp add: zero_enat_def)

lemma enat_1 [code_post]: "enat 1 = 1"
  by (simp add: one_enat_def)

lemma enat_0_iff: "enat x = 0 ⟷ x = 0" "0 = enat x ⟷ x = 0"
  by (auto simp add: zero_enat_def)

lemma enat_1_iff: "enat x = 1 ⟷ x = 1" "1 = enat x ⟷ x = 1"
  by (auto simp add: one_enat_def)

lemma one_eSuc: "1 = eSuc 0"
  by (simp add: zero_enat_def one_enat_def eSuc_def)

lemma infinity_ne_i0 [simp]: "(∞::enat) ≠ 0"
  by (simp add: zero_enat_def)

lemma i0_ne_infinity [simp]: "0 ≠ (∞::enat)"
  by (simp add: zero_enat_def)

lemma zero_one_enat_neq [simp]:
  "¬ 0 = (1::enat)"
  "¬ 1 = (0::enat)"
  unfolding zero_enat_def one_enat_def by simp_all

lemma infinity_ne_i1 [simp]: "(∞::enat) ≠ 1"
  by (simp add: one_enat_def)

lemma i1_ne_infinity [simp]: "1 ≠ (∞::enat)"
  by (simp add: one_enat_def)

lemma eSuc_enat: "eSuc (enat n) = enat (Suc n)"
  by (simp add: eSuc_def)

lemma eSuc_infinity [simp]: "eSuc ∞ = ∞"
  by (simp add: eSuc_def)

lemma eSuc_ne_0 [simp]: "eSuc n ≠ 0"
  by (simp add: eSuc_def zero_enat_def split: enat.splits)

lemma zero_ne_eSuc [simp]: "0 ≠ eSuc n"
  by (rule eSuc_ne_0 [symmetric])

lemma eSuc_inject [simp]: "eSuc m = eSuc n ⟷ m = n"
  by (simp add: eSuc_def split: enat.splits)

lemma eSuc_enat_iff: "eSuc x = enat y ⟷ (∃n. y = Suc n ∧ x = enat n)"
  by (cases y) (auto simp: enat_0 eSuc_enat[symmetric])

lemma enat_eSuc_iff: "enat y = eSuc x ⟷ (∃n. y = Suc n ∧ enat n = x)"
  by (cases y) (auto simp: enat_0 eSuc_enat[symmetric])

subsection ‹Addition›

instantiation enat :: comm_monoid_add
begin

definition [nitpick_simp]:
  "m + n = (case m of ∞ ⇒ ∞ | enat m ⇒ (case n of ∞ ⇒ ∞ | enat n ⇒ enat (m + n)))"

lemma plus_enat_simps [simp, code]:
  fixes q :: enat
  shows "enat m + enat n = enat (m + n)"
    and "∞ + q = ∞"
    and "q + ∞ = ∞"
  by (simp_all add: plus_enat_def split: enat.splits)

instance
proof
  fix n m q :: enat
  show "n + m + q = n + (m + q)"
    by (cases n m q rule: enat3_cases) auto
  show "n + m = m + n"
    by (cases n m rule: enat2_cases) auto
  show "0 + n = n"
    by (cases n) (simp_all add: zero_enat_def)
qed

end

lemma eSuc_plus_1:
  "eSuc n = n + 1"
  by (cases n) (simp_all add: eSuc_enat one_enat_def)
  
lemma plus_1_eSuc:
  "1 + q = eSuc q"
  "q + 1 = eSuc q"
  by (simp_all add: eSuc_plus_1 ac_simps)

lemma iadd_Suc: "eSuc m + n = eSuc (m + n)"
  by (simp_all add: eSuc_plus_1 ac_simps)

lemma iadd_Suc_right: "m + eSuc n = eSuc (m + n)"
  by (simp only: add.commute[of m] iadd_Suc)

lemma iadd_is_0: "(m + n = (0::enat)) = (m = 0 ∧ n = 0)"
  by (cases m, cases n, simp_all add: zero_enat_def)

subsection ‹Multiplication›

instantiation enat :: comm_semiring_1
begin

definition times_enat_def [nitpick_simp]:
  "m * n = (case m of ∞ ⇒ if n = 0 then 0 else ∞ | enat m ⇒
    (case n of ∞ ⇒ if m = 0 then 0 else ∞ | enat n ⇒ enat (m * n)))"

lemma times_enat_simps [simp, code]:
  "enat m * enat n = enat (m * n)"
  "∞ * ∞ = (∞::enat)"
  "∞ * enat n = (if n = 0 then 0 else ∞)"
  "enat m * ∞ = (if m = 0 then 0 else ∞)"
  unfolding times_enat_def zero_enat_def
  by (simp_all split: enat.split)

instance
proof
  fix a b c :: enat
  show "(a * b) * c = a * (b * c)"
    unfolding times_enat_def zero_enat_def
    by (simp split: enat.split)
  show "a * b = b * a"
    unfolding times_enat_def zero_enat_def
    by (simp split: enat.split)
  show "1 * a = a"
    unfolding times_enat_def zero_enat_def one_enat_def
    by (simp split: enat.split)
  show "(a + b) * c = a * c + b * c"
    unfolding times_enat_def zero_enat_def
    by (simp split: enat.split add: distrib_right)
  show "0 * a = 0"
    unfolding times_enat_def zero_enat_def
    by (simp split: enat.split)
  show "a * 0 = 0"
    unfolding times_enat_def zero_enat_def
    by (simp split: enat.split)
  show "(0::enat) ≠ 1"
    unfolding zero_enat_def one_enat_def
    by simp
qed

end

lemma mult_eSuc: "eSuc m * n = n + m * n"
  unfolding eSuc_plus_1 by (simp add: algebra_simps)

lemma mult_eSuc_right: "m * eSuc n = m + m * n"
  unfolding eSuc_plus_1 by (simp add: algebra_simps)

lemma of_nat_eq_enat: "of_nat n = enat n"
  apply (induct n)
  apply (simp add: enat_0)
  apply (simp add: plus_1_eSuc eSuc_enat)
  done

instance enat :: semiring_char_0
proof
  have "inj enat" by (rule injI) simp
  then show "inj (λn. of_nat n :: enat)" by (simp add: of_nat_eq_enat)
qed

lemma imult_is_0 [simp]: "((m::enat) * n = 0) = (m = 0 ∨ n = 0)"
  by (auto simp add: times_enat_def zero_enat_def split: enat.split)

lemma imult_is_infinity: "((a::enat) * b = ∞) = (a = ∞ ∧ b ≠ 0 ∨ b = ∞ ∧ a ≠ 0)"
  by (auto simp add: times_enat_def zero_enat_def split: enat.split)


subsection ‹Numerals›

lemma numeral_eq_enat:
  "numeral k = enat (numeral k)"
  using of_nat_eq_enat [of "numeral k"] by simp

lemma enat_numeral [code_abbrev]:
  "enat (numeral k) = numeral k"
  using numeral_eq_enat ..

lemma infinity_ne_numeral [simp]: "(∞::enat) ≠ numeral k"
  by (simp add: numeral_eq_enat)

lemma numeral_ne_infinity [simp]: "numeral k ≠ (∞::enat)"
  by (simp add: numeral_eq_enat)

lemma eSuc_numeral [simp]: "eSuc (numeral k) = numeral (k + Num.One)"
  by (simp only: eSuc_plus_1 numeral_plus_one)

subsection ‹Subtraction›

instantiation enat :: minus
begin

definition diff_enat_def:
"a - b = (case a of (enat x) ⇒ (case b of (enat y) ⇒ enat (x - y) | ∞ ⇒ 0)
          | ∞ ⇒ ∞)"

instance ..

end

lemma idiff_enat_enat [simp, code]: "enat a - enat b = enat (a - b)"
  by (simp add: diff_enat_def)

lemma idiff_infinity [simp, code]: "∞ - n = (∞::enat)"
  by (simp add: diff_enat_def)

lemma idiff_infinity_right [simp, code]: "enat a - ∞ = 0"
  by (simp add: diff_enat_def)

lemma idiff_0 [simp]: "(0::enat) - n = 0"
  by (cases n, simp_all add: zero_enat_def)

lemmas idiff_enat_0 [simp] = idiff_0 [unfolded zero_enat_def]

lemma idiff_0_right [simp]: "(n::enat) - 0 = n"
  by (cases n) (simp_all add: zero_enat_def)

lemmas idiff_enat_0_right [simp] = idiff_0_right [unfolded zero_enat_def]

lemma idiff_self [simp]: "n ≠ ∞ ⟹ (n::enat) - n = 0"
  by (auto simp: zero_enat_def)

lemma eSuc_minus_eSuc [simp]: "eSuc n - eSuc m = n - m"
  by (simp add: eSuc_def split: enat.split)

lemma eSuc_minus_1 [simp]: "eSuc n - 1 = n"
  by (simp add: one_enat_def eSuc_enat[symmetric] zero_enat_def[symmetric])

(*lemmas idiff_self_eq_0_enat = idiff_self_eq_0[unfolded zero_enat_def]*)

subsection ‹Ordering›

instantiation enat :: linordered_ab_semigroup_add
begin

definition [nitpick_simp]:
  "m ≤ n = (case n of enat n1 ⇒ (case m of enat m1 ⇒ m1 ≤ n1 | ∞ ⇒ False)
    | ∞ ⇒ True)"

definition [nitpick_simp]:
  "m < n = (case m of enat m1 ⇒ (case n of enat n1 ⇒ m1 < n1 | ∞ ⇒ True)
    | ∞ ⇒ False)"

lemma enat_ord_simps [simp]:
  "enat m ≤ enat n ⟷ m ≤ n"
  "enat m < enat n ⟷ m < n"
  "q ≤ (∞::enat)"
  "q < (∞::enat) ⟷ q ≠ ∞"
  "(∞::enat) ≤ q ⟷ q = ∞"
  "(∞::enat) < q ⟷ False"
  by (simp_all add: less_eq_enat_def less_enat_def split: enat.splits)

lemma numeral_le_enat_iff[simp]:
  shows "numeral m ≤ enat n ⟷ numeral m ≤ n"
by (auto simp: numeral_eq_enat)

lemma numeral_less_enat_iff[simp]:
  shows "numeral m < enat n ⟷ numeral m < n"
by (auto simp: numeral_eq_enat)

lemma enat_ord_code [code]:
  "enat m ≤ enat n ⟷ m ≤ n"
  "enat m < enat n ⟷ m < n"
  "q ≤ (∞::enat) ⟷ True"
  "enat m < ∞ ⟷ True"
  "∞ ≤ enat n ⟷ False"
  "(∞::enat) < q ⟷ False"
  by simp_all

instance
  by standard (auto simp add: less_eq_enat_def less_enat_def plus_enat_def split: enat.splits)

end

instance enat :: ordered_comm_semiring
proof
  fix a b c :: enat
  assume "a ≤ b" and "0 ≤ c"
  thus "c * a ≤ c * b"
    unfolding times_enat_def less_eq_enat_def zero_enat_def
    by (simp split: enat.splits)
qed

(* BH: These equations are already proven generally for any type in
class linordered_semidom. However, enat is not in that class because
it does not have the cancellation property. Would it be worthwhile to
a generalize linordered_semidom to a new class that includes enat? *)

lemma enat_ord_number [simp]:
  "(numeral m :: enat) ≤ numeral n ⟷ (numeral m :: nat) ≤ numeral n"
  "(numeral m :: enat) < numeral n ⟷ (numeral m :: nat) < numeral n"
  by (simp_all add: numeral_eq_enat)

lemma i0_lb [simp]: "(0::enat) ≤ n"
  by (simp add: zero_enat_def less_eq_enat_def split: enat.splits)

lemma ile0_eq [simp]: "n ≤ (0::enat) ⟷ n = 0"
  by (simp add: zero_enat_def less_eq_enat_def split: enat.splits)

lemma infinity_ileE [elim!]: "∞ ≤ enat m ⟹ R"
  by (simp add: zero_enat_def less_eq_enat_def split: enat.splits)

lemma infinity_ilessE [elim!]: "∞ < enat m ⟹ R"
  by simp

lemma not_iless0 [simp]: "¬ n < (0::enat)"
  by (simp add: zero_enat_def less_enat_def split: enat.splits)

lemma i0_less [simp]: "(0::enat) < n ⟷ n ≠ 0"
  by (simp add: zero_enat_def less_enat_def split: enat.splits)

lemma eSuc_ile_mono [simp]: "eSuc n ≤ eSuc m ⟷ n ≤ m"
  by (simp add: eSuc_def less_eq_enat_def split: enat.splits)
 
lemma eSuc_mono [simp]: "eSuc n < eSuc m ⟷ n < m"
  by (simp add: eSuc_def less_enat_def split: enat.splits)

lemma ile_eSuc [simp]: "n ≤ eSuc n"
  by (simp add: eSuc_def less_eq_enat_def split: enat.splits)

lemma not_eSuc_ilei0 [simp]: "¬ eSuc n ≤ 0"
  by (simp add: zero_enat_def eSuc_def less_eq_enat_def split: enat.splits)

lemma i0_iless_eSuc [simp]: "0 < eSuc n"
  by (simp add: zero_enat_def eSuc_def less_enat_def split: enat.splits)

lemma iless_eSuc0[simp]: "(n < eSuc 0) = (n = 0)"
  by (simp add: zero_enat_def eSuc_def less_enat_def split: enat.split)

lemma ileI1: "m < n ⟹ eSuc m ≤ n"
  by (simp add: eSuc_def less_eq_enat_def less_enat_def split: enat.splits)

lemma Suc_ile_eq: "enat (Suc m) ≤ n ⟷ enat m < n"
  by (cases n) auto

lemma iless_Suc_eq [simp]: "enat m < eSuc n ⟷ enat m ≤ n"
  by (auto simp add: eSuc_def less_enat_def split: enat.splits)

lemma imult_infinity: "(0::enat) < n ⟹ ∞ * n = ∞"
  by (simp add: zero_enat_def less_enat_def split: enat.splits)

lemma imult_infinity_right: "(0::enat) < n ⟹ n * ∞ = ∞"
  by (simp add: zero_enat_def less_enat_def split: enat.splits)

lemma enat_0_less_mult_iff: "(0 < (m::enat) * n) = (0 < m ∧ 0 < n)"
  by (simp only: i0_less imult_is_0, simp)

lemma mono_eSuc: "mono eSuc"
  by (simp add: mono_def)


lemma min_enat_simps [simp]:
  "min (enat m) (enat n) = enat (min m n)"
  "min q 0 = 0"
  "min 0 q = 0"
  "min q (∞::enat) = q"
  "min (∞::enat) q = q"
  by (auto simp add: min_def)

lemma max_enat_simps [simp]:
  "max (enat m) (enat n) = enat (max m n)"
  "max q 0 = q"
  "max 0 q = q"
  "max q ∞ = (∞::enat)"
  "max ∞ q = (∞::enat)"
  by (simp_all add: max_def)

lemma enat_ile: "n ≤ enat m ⟹ ∃k. n = enat k"
  by (cases n) simp_all

lemma enat_iless: "n < enat m ⟹ ∃k. n = enat k"
  by (cases n) simp_all

lemma iadd_le_enat_iff:
  "x + y ≤ enat n ⟷ (∃y' x'. x = enat x' ∧ y = enat y' ∧ x' + y' ≤ n)"
by(cases x y rule: enat.exhaust[case_product enat.exhaust]) simp_all

lemma chain_incr: "∀i. ∃j. Y i < Y j ==> ∃j. enat k < Y j"
apply (induct_tac k)
 apply (simp (no_asm) only: enat_0)
 apply (fast intro: le_less_trans [OF i0_lb])
apply (erule exE)
apply (drule spec)
apply (erule exE)
apply (drule ileI1)
apply (rule eSuc_enat [THEN subst])
apply (rule exI)
apply (erule (1) le_less_trans)
done

lemma eSuc_max: "eSuc (max x y) = max (eSuc x) (eSuc y)"
  by (simp add: eSuc_def split: enat.split)

lemma eSuc_Max: 
  assumes "finite A" "A ≠ {}"
  shows "eSuc (Max A) = Max (eSuc ` A)"
using assms proof induction
  case (insert x A)
  thus ?case by(cases "A = {}")(simp_all add: eSuc_max)
qed simp

instantiation enat :: "{order_bot, order_top}"
begin

definition bot_enat :: enat where "bot_enat = 0"
definition top_enat :: enat where "top_enat = ∞"

instance
  by standard (simp_all add: bot_enat_def top_enat_def)

end

lemma finite_enat_bounded:
  assumes le_fin: "⋀y. y ∈ A ⟹ y ≤ enat n"
  shows "finite A"
proof (rule finite_subset)
  show "finite (enat ` {..n})" by blast
  have "A ⊆ {..enat n}" using le_fin by fastforce
  also have "… ⊆ enat ` {..n}"
    apply (rule subsetI)
    subgoal for x by (cases x) auto
    done
  finally show "A ⊆ enat ` {..n}" .
qed


subsection ‹Cancellation simprocs›

lemma enat_add_left_cancel: "a + b = a + c ⟷ a = (∞::enat) ∨ b = c"
  unfolding plus_enat_def by (simp split: enat.split)

lemma enat_add_left_cancel_le: "a + b ≤ a + c ⟷ a = (∞::enat) ∨ b ≤ c"
  unfolding plus_enat_def by (simp split: enat.split)

lemma enat_add_left_cancel_less: "a + b < a + c ⟷ a ≠ (∞::enat) ∧ b < c"
  unfolding plus_enat_def by (simp split: enat.split)

ML ‹
structure Cancel_Enat_Common =
struct
  (* copied from src/HOL/Tools/nat_numeral_simprocs.ML *)
  fun find_first_t _    _ []         = raise TERM("find_first_t", [])
    | find_first_t past u (t::terms) =
          if u aconv t then (rev past @ terms)
          else find_first_t (t::past) u terms

  fun dest_summing (Const (@{const_name Groups.plus}, _) $ t $ u, ts) =
        dest_summing (t, dest_summing (u, ts))
    | dest_summing (t, ts) = t :: ts

  val mk_sum = Arith_Data.long_mk_sum
  fun dest_sum t = dest_summing (t, [])
  val find_first = find_first_t []
  val trans_tac = Numeral_Simprocs.trans_tac
  val norm_ss =
    simpset_of (put_simpset HOL_basic_ss @{context}
      addsimps @{thms ac_simps add_0_left add_0_right})
  fun norm_tac ctxt = ALLGOALS (simp_tac (put_simpset norm_ss ctxt))
  fun simplify_meta_eq ctxt cancel_th th =
    Arith_Data.simplify_meta_eq [] ctxt
      ([th, cancel_th] MRS trans)
  fun mk_eq (a, b) = HOLogic.mk_Trueprop (HOLogic.mk_eq (a, b))
end

structure Eq_Enat_Cancel = ExtractCommonTermFun
(open Cancel_Enat_Common
  val mk_bal = HOLogic.mk_eq
  val dest_bal = HOLogic.dest_bin @{const_name HOL.eq} @{typ enat}
  fun simp_conv _ _ = SOME @{thm enat_add_left_cancel}
)

structure Le_Enat_Cancel = ExtractCommonTermFun
(open Cancel_Enat_Common
  val mk_bal = HOLogic.mk_binrel @{const_name Orderings.less_eq}
  val dest_bal = HOLogic.dest_bin @{const_name Orderings.less_eq} @{typ enat}
  fun simp_conv _ _ = SOME @{thm enat_add_left_cancel_le}
)

structure Less_Enat_Cancel = ExtractCommonTermFun
(open Cancel_Enat_Common
  val mk_bal = HOLogic.mk_binrel @{const_name Orderings.less}
  val dest_bal = HOLogic.dest_bin @{const_name Orderings.less} @{typ enat}
  fun simp_conv _ _ = SOME @{thm enat_add_left_cancel_less}
)
›

simproc_setup enat_eq_cancel
  ("(l::enat) + m = n" | "(l::enat) = m + n") =
  ‹fn phi => fn ctxt => fn ct => Eq_Enat_Cancel.proc ctxt (Thm.term_of ct)›

simproc_setup enat_le_cancel
  ("(l::enat) + m ≤ n" | "(l::enat) ≤ m + n") =
  ‹fn phi => fn ctxt => fn ct => Le_Enat_Cancel.proc ctxt (Thm.term_of ct)›

simproc_setup enat_less_cancel
  ("(l::enat) + m < n" | "(l::enat) < m + n") =
  ‹fn phi => fn ctxt => fn ct => Less_Enat_Cancel.proc ctxt (Thm.term_of ct)›

text ‹TODO: add regression tests for these simprocs›

text ‹TODO: add simprocs for combining and cancelling numerals›

subsection ‹Well-ordering›

lemma less_enatE:
  "[| n < enat m; !!k. n = enat k ==> k < m ==> P |] ==> P"
by (induct n) auto

lemma less_infinityE:
  "[| n < ∞; !!k. n = enat k ==> P |] ==> P"
by (induct n) auto

lemma enat_less_induct:
  assumes prem: "!!n. ∀m::enat. m < n --> P m ==> P n" shows "P n"
proof -
  have P_enat: "!!k. P (enat k)"
    apply (rule nat_less_induct)
    apply (rule prem, clarify)
    apply (erule less_enatE, simp)
    done
  show ?thesis
  proof (induct n)
    fix nat
    show "P (enat nat)" by (rule P_enat)
  next
    show "P ∞"
      apply (rule prem, clarify)
      apply (erule less_infinityE)
      apply (simp add: P_enat)
      done
  qed
qed

instance enat :: wellorder
proof
  fix P and n
  assume hyp: "(⋀n::enat. (⋀m::enat. m < n ⟹ P m) ⟹ P n)"
  show "P n" by (blast intro: enat_less_induct hyp)
qed

subsection ‹Complete Lattice›

instantiation enat :: complete_lattice
begin

definition inf_enat :: "enat ⇒ enat ⇒ enat" where
  "inf_enat = min"

definition sup_enat :: "enat ⇒ enat ⇒ enat" where
  "sup_enat = max"

definition Inf_enat :: "enat set ⇒ enat" where
  "Inf_enat A = (if A = {} then ∞ else (LEAST x. x ∈ A))"

definition Sup_enat :: "enat set ⇒ enat" where
  "Sup_enat A = (if A = {} then 0 else if finite A then Max A else ∞)"
instance
proof
  fix x :: "enat" and A :: "enat set"
  { assume "x ∈ A" then show "Inf A ≤ x"
      unfolding Inf_enat_def by (auto intro: Least_le) }
  { assume "⋀y. y ∈ A ⟹ x ≤ y" then show "x ≤ Inf A"
      unfolding Inf_enat_def
      by (cases "A = {}") (auto intro: LeastI2_ex) }
  { assume "x ∈ A" then show "x ≤ Sup A"
      unfolding Sup_enat_def by (cases "finite A") auto }
  { assume "⋀y. y ∈ A ⟹ y ≤ x" then show "Sup A ≤ x"
      unfolding Sup_enat_def using finite_enat_bounded by auto }
qed (simp_all add:
 inf_enat_def sup_enat_def bot_enat_def top_enat_def Inf_enat_def Sup_enat_def)
end

instance enat :: complete_linorder ..

lemma eSuc_Sup: "A ≠ {} ⟹ eSuc (Sup A) = Sup (eSuc ` A)"
  by(auto simp add: Sup_enat_def eSuc_Max inj_on_def dest: finite_imageD)

lemma sup_continuous_eSuc: "sup_continuous f ⟹ sup_continuous (λx. eSuc (f x))"
  using  eSuc_Sup[of "_ ` UNIV"] by (auto simp: sup_continuous_def)

subsection ‹Traditional theorem names›

lemmas enat_defs = zero_enat_def one_enat_def eSuc_def
  plus_enat_def less_eq_enat_def less_enat_def

end